2011
DOI: 10.1111/j.1365-2966.2011.19261.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties of z∼ 0.5 absorption-selected galaxies: the role of galaxy inclination

Abstract: We have used Galaxy IMage 2D (GIM2D) to quantify the morphological properties of 40 intermediate‐redshift Mg ii absorption‐selected galaxies [0.03 ≤ Wr(2796) ≤ 2.9 Å], imaged with WFPC‐2/Hubble Space Telescope (HST), and compared them to the halo gas properties measured from HIRES/Keck and UVES/VLT quasar spectra. We find that as the quasar–galaxy separation, D, increases the Mg ii equivalent decreases with large scatter, implying that D is not the only physical parameter affecting the distribution and quantit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 82 publications
(202 reference statements)
8
100
0
Order By: Relevance
“…The inclination is sin i=0.87±0.01, i.e. slightly higher than the one reported by Kacprzak et al (2011) from a GIM2D modelling of HST observations (sin i=0.75±0.05). These results are collected in Table 5.…”
Section: Morphological and Kinematical Propertiesmentioning
confidence: 71%
See 1 more Smart Citation
“…The inclination is sin i=0.87±0.01, i.e. slightly higher than the one reported by Kacprzak et al (2011) from a GIM2D modelling of HST observations (sin i=0.75±0.05). These results are collected in Table 5.…”
Section: Morphological and Kinematical Propertiesmentioning
confidence: 71%
“…This was the first spectroscopic confirmation of a galaxy associated with a quasar absorber. Kacprzak et al (2011) used HST/WFPC2 F702W archival data shown in Figure 3 and reported a B-band absolute magnitude MB = −20.32 and a corresponding luminosity of 0.46L * . They further studied the morphological properties of the object using GIM2D modelling (Simard et al 2002) (Pettini & Pagel 2004).…”
Section: Imaging: a Large Galaxymentioning
confidence: 99%
“…One of the easiest species to detect is the Mg ii λλ2796, 2804 doublet, which is frequently in combination with Fe ii λλ2587, 2600, Fe ii λλ2374, 2382, Fe ii λ2344, and Mg i λ2853. While the origin of the absorbing gas remains unclear, a direct association with galaxies is suggested by several studies (e.g., Bahcall & Spitzer 1969;Steidel et al 1997;Bowen & Chelouche 2011;Kacprzak et al 2011). Dust embedded in foreground absorber systems along the line of sight is expected to absorb and scatter the UV photons from the quasar and redden the quasar spectrum.…”
Section: Intervening Absorbersmentioning
confidence: 99%
“…Several HST programs have exploited this new capability to investigate the gaseous environments of a sample of low-z haloes, including COS-Halos (Tumlinson et al 2013), COS-Dwarfs (Bordoloi et al 2014), and COS-GASS (Borthakur et al 2015). Other recent studies have also characterized the CGM relative to samples of galaxies, including Chen et al (2010), Bordoloi et al (2011), Kacprzak et al (2011Kacprzak et al ( , 2015, Borthakur et al (2013), Churchill et al (2013), , Stocke et al (2013), Liang & Chen (2014) at low-z and Turner et al (2014) at high-z.…”
mentioning
confidence: 99%